Managing Organizational Inertia: Indonesian Family Business Perspective - Teofilus, Teofilus; Ardyan, Elia; Sutrisno, Timotius F. C. W.; Sabar, Sabar; Sutanto, Verrell (Frontiers in Psychology, 2022)
Periodical transformations are very crucial as an effort to adapt to environmental challenges, however, alteration in core features of an organization may increase the chance of failure. Therefore, organizational reconfiguration efforts, in this phenomenon particularly, seem to engender cynicism as one of the most significant challenges for contemporary organizations. This resistance to change and the tendency to maintain the status quo would then give rise to a term known as organizational inertia. Concerning this phenomenon, massive social, economic, and technological challenges require companies to apply the concept of empowering leadership in order to stimulate a new organizational culture that is able to oppose the occurrence of organizational inertia. This research was conducted with the aim of developing a framework that discusses the phenomenon of cynicism about organizational change, which focuses on dispositional attribution, as antecedents for organizational inertia moderated by empowering leadership in the context of the family business within the framework of attribution theory. The population of this study is family-owned businesses in Indonesia, with a total of 31 family businesses, which are spread over the islands of Java, Sumatra, Kalimantan, and Sulawesi. In addition, this research is multisource, in which the types of respondents were top management team member and employee of each family business. The results of this research indicate that cynicism about organizational change has a positive and significant effect on organizational inertia but negative on sustainable family business. In relation to this empowering leadership mechanism, top level management must provide development support to lower levels of management. In addition, top level management has to provide not only development support but also power sharing and motivational support to middle level of management.